Public Perception and Reaction Toward Early-Age Marriage (Case: Village of Arajang, Region of Wajo) - Bunyamin Bunyamin; Riska Novita; Mujahidin Mujahidin (SAPIENTIA ET VIRTUS, 2023)
The practice of early-age marriage has been observed to have a multitude of adverse effects on various domains, including mental health, physical health, education, productivity, and most significantly, the quality of human resources in the future. The practice of early-age marriage has been observed in various locations, including the village of Arajang in the Wajo region. The legality of early-age marriage is addressed in National Law No.16 of 2019, which stipulates that marriage is only permissible when both people involved have attained the age of 19. However, it is important to note that the actual findings diverge significantly. This study employed a qualitative approach, utilizing open interviews as the primary technique of data collection. Additionally, deductive reasoning was employed in the analysis of the gathered data. This research has identified several factors that influence early-age marriage, including cultural and traditional practices, levels of knowledge and education, instances of adultery, and economic and poverty-related concerns. Another outcome of this study indicates that the residents of Arajang do not exhibit concerns regarding early-age marriage. Consequently, there is a pressing necessity to undertake comprehensive educational initiatives to raise awareness about the consequences of child marriage.